Tailoring of ketoprofen particle morphology via novel crystallocoagglomeration technique to obtain a directly compressible material - Chavda, Vikash; Maheshwari, Rajesh Kumar (Asian Journal of Pharmaceutics (AJP), 2014)
Purpose: The purpose of this research was to develop a novel crystallo-co-agglomeration (CCA) method for ketoprofen to obtain its directly compressible spherical agglomerates with improved flowability and compressibility. Methodology: Dichloromethane-water system containing polyethylene glycol (PEG) 6000, polyvinyl alcohol (PVA), and hydroxypropylmethylcellulose (HPMC) 100 Centi Poise was used as the crystallization system. Ketoprofen was crystallized from dichloromethane and agglomerated with talc. Experimental parameters (concentration of PEG, PVA, and HPMC; effect of temperature; and agitation speed) were optimized. The agglomerates were evaluated for micrometric properties, mechanical properties, moisture content, compressibility, packability, and drug-release properties. The agglomerates were characterized by differential scanning calorimetry (DSC), powder x-ray diffraction (PXRD), infrared (IR) spectroscopy, and scanning electron microscopy (SEM). Main Findings: Remarkable improvement in micromeritic properties (angle of repose <22Â°, percentage compressibility <10, and Hausner ratio near to 1) and compactibility (mean yield pressure 55-93 MPa) enabled direct compression without any defect. Results of friability showed higher surface strength of agglomerates containing higher amount of talc. DSC, PXRD, and IR results showed no change in the crystalline form of ketoprofen. Dissolution study of batches KA, KB, KC, and KD(composition given in Table 1) showed 90% drug release in 120, 180, 240, and 420 min respectively. Principal Conclusions: Crystallo-co-agglomeration process can be considered as a suitable alternative to conventional granulation process to obtain agglomerates of ketoprofen with improved micromeritic and compressibility parameters. The CCA technique can be used for the design of sustained-release ketoprofen talc agglomerates containing lower amounts of polymers.